Transfer pricing in multinational firms : a heuristic programming approach and a case study - Nieckels, Lars. (Stockholm : Almqvist & Wiksell International ; New York : Halsted Press, 1976)
This book examines resource allocation and transfer price problem in a centralised multinational firm in order to optimize both, including the costs of taxes and duties. Discusses the characteristics of multinationals, reviews traditional transfer pricing, and describes three models of a multinational firm facing resource allocation and transfer price problems. A heuristic solution procedure is then described and ways of determining its closeness to the global optimum are outlined. This solution procedure is then applied to a company in the textile industry. The conclusion and summary emphasises the treatment of transfer prices as real decision variables.
Includes index.
Includes bibliographical references: p. 177-181.
lje 23/04/2018
Loans
Keywords: International business enterprises; Transfer pricing; Heuristic programming